Towards a better framework for estimative intelligence – addressing quality through a systematic approach to uncertainty handling - Isaksen, Bjorn G. M.; McNaught, Ken R. (Taylor & Francis, 2023)
The analytic standards governing the production of intelligence are outlined in a number of Intelligence Community Directives (ICDs). In this paper, we are concerned with ICDs 203, 206 and 208 and, in particular, how these relate to the handling of uncertainty in estimative intelligence. An inductive thematic analysis is employed which identifies several recurring themes. In addition, a conceptual map is developed which highlights relationships and the level of inter-connectedness between the standards. Requirements for improved operationalization of uncertainty handling are also discussed. The question of analytic feasibility is then examined in relation to the five themes extracted from the earlier analysis. The paper concludes that a new framework for uncertainty handling is required and suggests that such a framework should contain a process to assess analytic feasibility from the outset of a study.